Uncertainties in the modelled CO 2 threshold for Antarctic glaciation - E. Gasson; D. J. Lunt; R. DeConto; A. Goldner; M. Heinemann; M. Huber; A. N. LeGrande; D. Pollard; N. Sagoo; M. Siddall; A. Winguth; P. J. Valdes (Climate of the Past, 2014)
A frequently cited atmospheric CO 2 threshold for the onset of Antarctic glaciation of ~780 ppmv is based on the study of DeConto and Pollard (2003) using an ice sheet model and the GENESIS climate model. Proxy records suggest that atmospheric CO 2 concentrations passed through this threshold across the Eocene–Oligocene transition ~34 Ma. However, atmospheric CO 2 concentrations may have been close to this threshold earlier than this transition, which is used by some to suggest the possibility of Antarctic ice sheets during the Eocene. Here we investigate the climate model dependency of the threshold for Antarctic glaciation by performing offline ice sheet model simulations using the climate from 7 different climate models with Eocene boundary conditions (HadCM3L, CCSM3, CESM1.0, GENESIS, FAMOUS, ECHAM5 and GISS_ER). These climate simulations are sourced from a number of independent studies, and as such the boundary conditions, which are poorly constrained during the Eocene, are not identical between simulations. The results of this study suggest that the atmospheric CO 2 threshold for Antarctic glaciation is highly dependent on the climate model used and the climate model configuration. A large discrepancy between the climate model and ice sheet model grids for some simulations leads to a strong sensitivity to the lapse rate parameter.